Challenging cisgenderism through trans people's narratives of domestic violence and abuse. (September 2019) - Rogers, Michaela
By drawing on empirical research that explored trans people's experiences of domestic violence and abuse (DVA), this article problematises the 'gender asymmetry debate' in DVA discourse. It does so by highlighting cisgenderism and a heteronormative bias, which have led to the invisibility of a trans perspective. Qualitative data was collected via narrative interviews and this was examined using a voice-centred relational technique. A total of 24 interviews were undertaken with trans people ( n = 15) and domestic abuse practitioners ( n = 9). In relation to the presentation and impact of DVA, and in the context of trans and cisgender people's abuse experiences, the research findings report both similarities and differences. Four narratives are presented here to illuminate both. This article adds new insight and challenges normative and dominant discourses by promoting the need for further theorising about the gendered nature of domestic violence and abuse.